2016
DOI: 10.1097/sga.0000000000000224
|View full text |Cite
|
Sign up to set email alerts
|

Constipation: Prevalence and Associated Factors in Adults Living in Londrina, Southern Brazil

Abstract: The aims of this study were to estimate the prevalence of constipation and identify associated factors among adults living in an urban area in Londrina, Brazil. This was a secondary analysis of an epidemiological, population-based study on bowel habit performed in 2008 with 2,162 individuals selected through cluster sampling. Interviews were administered using a sociodemographic questionnaire and the adapted and validated Brazilian version of the "Bowel Function in the Community" tool. Variables from the origi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…Only one study has shown a greater prevalence in males where the F/M ratio was 0.84[ 50 ]. Odds ratios for chronic constipation in females were reported as 2.22 in a global systematic review[ 36 ] and ranged from 1.0 to 4.8 in epidemiological studies[ 46 , 47 , 51 , 53 , 54 , 60 , 64 - 66 ].…”
Section: Demographic and Socioeconomic Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Only one study has shown a greater prevalence in males where the F/M ratio was 0.84[ 50 ]. Odds ratios for chronic constipation in females were reported as 2.22 in a global systematic review[ 36 ] and ranged from 1.0 to 4.8 in epidemiological studies[ 46 , 47 , 51 , 53 , 54 , 60 , 64 - 66 ].…”
Section: Demographic and Socioeconomic Factorsmentioning
confidence: 99%
“…For chronic constipation, a Canadian study showed evidence of an inverse relationship[ 45 ] but this was not the case in a United States study[ 68 ]. In Iran and Brazil, there was significantly higher prevalence in those with lower income[ 52 , 66 ] but there was no inverse relationship in South Korea[ 58 ] and Hong Kong[ 57 ]. An inverse relationship was also reported in an Australian study[ 82 ].…”
Section: Demographic and Socioeconomic Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…A systematic review of 10 studies conducted in Iranian adult populations showed that the prevalence of any constipation ranged from 1.4% to 37% and the prevalence of chronic constipation based on either Rome II or Rome III criteria ranged from 2.4% to 11.2%. [61] 4.1.5 South America Four studies, [24,53,62,63] have estimated prevalence in Brazil, Argentina and Colombia (see Table 2). In Brazil, prevalence ranged from 9.7% [62] when defined as <3BM/week to 14.6% [63] when using modified Rome III criteria to 16.7% for self-reported constipation.…”
Section: Asiamentioning
confidence: 99%
“…[61] 4.1.5 South America Four studies, [24,53,62,63] have estimated prevalence in Brazil, Argentina and Colombia (see Table 2). In Brazil, prevalence ranged from 9.7% [62] when defined as <3BM/week to 14.6% [63] when using modified Rome III criteria to 16.7% for self-reported constipation. [24] 4.1.6 Australia Australia exemplifies the problem where a number of different studies in the same country have produced a wide range of prevalence estimates so it is difficult to determine the true prevalence (see Table 2).…”
Section: Asiamentioning
confidence: 99%